Examining Relationships Between Factors of Science Education and Student Career Aspiration - Wang, Jianjun; Staver, John R. (The Journal of educational research (Washington, D.C.), 2001)
Student career aspiration has been identified as the most important variable influencing students' later work experiences. The authors attempted to disentangle relationships among factors that influence career aspiration within a science education context. Guided by Walberg's (1981) educational productivity theory, factors of science education have been identified from a National Science Foundation project, the Longitudinal Study of American Youth. Career aspirations are represented by 2 indicators: expected jobs in the future and job demands on science literacy. Positive links were found between student career aspiration and several variables of science education, including educational outcomes, instructional quantity, and home environment. Implications of the results have been discussed to facilitate development of career aspiration among non-college-bound students.